Antistatic master batch, preparation method thereof and antistatic sheet
By using a combination of polystyrene resin, polysiloxane resin, and modified carbon black and carbon nanotubes, the problem of unstable performance of carbon black masterbatches is solved, and the antistatic performance and overall performance of electronic carrier tape are improved.
Patent Information
- Application Number
- CN202411217953.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-10
AI Technical Summary
The existing carbon black masterbatches are used in electronic carrier tapes in large quantities and are prone to fall off, resulting in surface dust loss and particle defects, affecting the performance of electronic carrier tapes.
Antistatic masterbatches using polystyrene resin, polysiloxane resin, modified carbon black and modified carbon nanotubes are improved through pretreatment and dispersant combination, and the dispersion performance of carbon black and carbon nanotubes is reduced. The production of particles and insoluble matter.
It has achieved improvements in antistatic properties, reduced surface ash loss and particle problems, improved the performance of electronic carrier tape and the simplicity of industrial production.
Smart Images

Figure CN119286157A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of composite materials, and specifically relates to an antistatic masterbatch and a preparation method thereof, and an antistatic sheet. Background Art
[0002] With the development of science and technology, electronic carriers have been increasingly studied and applied. Antistatic sheets can be used to make electronic carriers. Since electronic carriers can be used to hold electronic chips, they need to have extremely high antistatic properties and surface cleanliness. Commonly used antistatic carriers mostly use carbon black as an antistatic agent. Carbon black requires a large amount of use and is easy to fall off, which limits the application of electronic carriers.
[0003] In order to solve the problem that carbon black is used in large amounts and is easy to fall off in electronic carriers, currently carbon black powder is made into carbon black masterbatch in advance, and the carbon black masterbatch also contains resin, etc. However, due to the high aggregation and lipophilicity of carbon black powder, the existing carbon black masterbatch formula and / or process often leads to unstable performance, resulting in defects such as surface dusting and particles when making antistatic sheets, which in turn makes the performance of electronic carriers poor.
[0004] Therefore, how to prepare high-performance carbon black masterbatch has always been a very challenging problem. Summary of the invention
[0005] The purpose of the present application is to overcome the above-mentioned deficiencies in the prior art and to provide an antistatic masterbatch and a preparation method thereof, as well as an antistatic sheet. The antistatic masterbatch can solve the problem that the performance of the existing carbon black masterbatch is unstable, resulting in the defects of surface dusting and particles when the antistatic sheet is made using the masterbatch, thereby causing the problem of poor performance of the electronic carrier.
[0006] In order to achieve the above application purpose, the first aspect of the present application provides an antistatic masterbatch, which comprises, by weight:
[0007] Polystyrene resin, 30-40 parts;
[0008] Polysiloxane resin, 15-30 parts;
[0009] Modified carbon black, 40-60 parts; wherein the modified carbon black is acid-modified carbon black;
[0010] 5 to 20 parts of modified carbon nanotubes; wherein the modified carbon nanotubes are carbon nanotubes modified by surfactants;
[0011] Combined dispersant, 15 to 30 parts.
[0012] Furthermore, the percentage of the modified carbon black and the modified carbon nanotube in the total amount of the antistatic masterbatch is in the range of 50 to 60%;
[0013] and / or,
[0014] The melt mass flow rate of the antistatic masterbatch is greater than 70 g / 10 min.
[0015] Furthermore, the surfactant includes at least one of alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, and high-carbon fatty alcohol polyoxyethylene ether.
[0016] Furthermore, the polysiloxane resin includes polydimethylsiloxane.
[0017] Furthermore, the combined dispersant comprises oxidized polyethylene wax and a random copolymer, and the random copolymer is formed by copolymerization of an aromatic vinyl monomer and an acrylonitrile monomer.
[0018] Furthermore, the mass percentage range of the oxidized polyethylene wax and the random copolymer is 2-4:2-1.
[0019] The second aspect of the present application provides an antistatic sheet material, comprising the above-mentioned antistatic masterbatch.
[0020] The third aspect of the present application provides a method for preparing the above-mentioned antistatic masterbatch, comprising the following steps:
[0021] The modified carbon black, the modified carbon nanotubes and the combined dispersant are uniformly mixed and dispersed to obtain a conductive mixture;
[0022] The conductive mixture, a part of the polystyrene resin and all the polysiloxane resin are uniformly mixed, heated and kneaded, and then sliced to obtain a sliced material;
[0023] The sliced material and the remaining part of the polystyrene resin are blended, melted, extruded and granulated to obtain the antistatic masterbatch.
[0024] Further, the maximum particle size of the conductive mixture is less than or equal to 50 nm;
[0025] and / or,
[0026] The amount of the part of polystyrene resin used in the total mass percentage of the whole polystyrene resin is in the range of 30 to 50%.
[0027] Furthermore, the preparation method of the modified carbon black comprises the following steps:
[0028] The carbon black and concentrated acid are mixed evenly at 60-130°C, washed to neutrality, and dried to obtain oxidized carbon black;
[0029] The oxidized carbon black, the terminal hydroxyl polydimethylsiloxane and the catalyst are uniformly mixed at 50 to 140° C. to obtain the modified carbon black.
[0030] Furthermore, the preparation method of the modified carbon nanotubes comprises the following steps:
[0031] dissolving a surfactant in water to obtain a surfactant aqueous solution;
[0032] Adding carbon nanotubes to the surfactant aqueous solution, mixing evenly, and ultrasonically treating for a period of time to obtain a suspension;
[0033] The suspension is heated and refluxed for a period of time, and then the powder is filtered out and vacuum dried to obtain the modified carbon nanotubes.
[0034] Compared with the prior art, this application has the following technical effects:
[0035] The present application provides an antistatic masterbatch, a preparation method thereof, and an antistatic sheet. The antistatic masterbatch is prepared by selecting polystyrene resin and polysiloxane resin as the resins of the antistatic masterbatch. In this case, the polysiloxane resin can serve as an auxiliary agent for the polystyrene resin to improve the extrusion processing performance of the polystyrene resin. At the same time, the combined dispersant can also improve the dispersion performance of the modified carbon black and the modified carbon nanotubes. By pretreating the carbon black into modified carbon black and the carbon nanotubes into modified carbon nanotubes, the dispersion effect of the combined dispersant can also be coordinated, thereby greatly improving the dispersion performance of the carbon black and the carbon nanotubes, and effectively reducing the generation of particles, insoluble matter, etc. of carbon black and carbon nanotubes, so that the antistatic performance of the sheet using the antistatic masterbatch is also good. In addition, the preparation method is simple and easy to implement, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0037] Figure 1 A process flow chart of the preparation of an antistatic masterbatch provided in an embodiment of the present application;
[0038] Figure 2 A flow chart of another preparation process of antistatic masterbatch provided in an embodiment of the present application;
[0039] Figure 3 A process flow chart of the preparation of modified carbon black provided in the embodiments of the present application;
[0040] Figure 4 A process flow chart for preparing modified carbon nanotubes provided in an embodiment of the present application. DETAILED DESCRIPTION
[0041] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0042] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0043] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or multiple, respectively.
[0044] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0045] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0046] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be a well-known mass unit such as μg, mg, g, kg, etc.
[0047] The terms "first", "second", etc. are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features.
[0048] In the first aspect, an embodiment of the present application provides an antistatic masterbatch, which includes, by weight: 30 to 40 parts of polystyrene resin (PS); 15 to 30 parts of polysiloxane resin; 40 to 60 parts of modified carbon black; wherein the modified carbon black is acid-modified carbon black; 5 to 20 parts of modified carbon nanotubes; wherein the modified carbon nanotubes are surfactant-modified carbon nanotubes; and 15 to 30 parts of a combined dispersant.
[0049] Furthermore, the antistatic masterbatch may further include: an antioxidant, 1 to 3 parts by weight.
[0050] There is no specific limitation on the number of parts by weight of the PS resin. For example, the number of parts of the PS resin can be 30 parts, 32 parts, 34 parts, 36 parts, 38 parts or 40 parts, etc.; there is no specific limitation on the number of parts by weight of the polysiloxane resin. For example, the number of parts of the polysiloxane resin can be 15 parts, 18 parts, 20 parts, 23 parts, 26 parts or 30 parts, etc.; there is no specific limitation on the number of parts by weight of the modified carbon black. For example, the number of parts of the modified carbon black can be 40 parts, 48 parts, 50 parts, 53 parts, 56 parts or 57 parts. or 60 parts, etc.; there is no specific limitation on the number of the modified carbon nanotubes by weight, and illustratively, the modified carbon nanotubes can be 5 parts, 8 parts, 10 parts, 13 parts, 16 parts or 20 parts, etc.; there is no specific limitation on the number of the combined dispersants by weight, and illustratively, the combined dispersants can be 15 parts, 16 parts, 20 parts, 25 parts, 28 parts or 30 parts, etc.; there is no specific limitation on the number of the antioxidants by weight, and illustratively, the antioxidants can be 2 parts, 3 parts, 4 parts, 5 parts or 6 parts, etc.
[0051] In practical applications, the PS resin can be used to prepare antistatic PS sheets. Meanwhile, the antistatic PS sheets also include a matrix resin, and the PS resin can improve the compatibility of the antistatic masterbatch with the matrix resin in the PS sheets.
[0052] On the basis of the above, polysiloxane resin and PS resin are used in combination as the resin of the antistatic masterbatch, wherein the polysiloxane resin may include polydimethylsiloxane and the like.
[0053] In this way, on the one hand, polydimethylsiloxane has a high compatibility with modified carbon black, which can achieve good dispersion of carbon black in the antistatic masterbatch; on the other hand, polydimethylsiloxane can also improve the processing performance of PS resin extrusion when preparing PS sheets. Specifically, during the extrusion production process, polydimethylsiloxane can form a stable dynamic coating on the inner wall of the die, which effectively reduces the force between the molten melt and the die surface, and reduces the excessive stretching and orientation of the polymer chains of the sheet PS resin, thereby achieving the purpose of reducing die accumulation and improving processing performance.
[0054] In practical applications, the acid-modified carbon black can be obtained by mixing carbon black powder and concentrated acid at a certain temperature, washing to neutrality, and drying to obtain oxidized carbon black, which is then mixed with terminal hydroxyl polydimethylsiloxane and a catalyst at a certain temperature.
[0055] The concentrated acid here may include concentrated nitric acid, concentrated sulfuric acid, concentrated hydrochloric acid, etc. The concentrated acid can increase the surface functional groups and defects of the carbon black powder, thereby improving the dispersibility of the modified carbon black in the antistatic masterbatch.
[0056] The catalyst used here is a catalyst that catalyzes the reaction between carboxyl and hydroxyl, for example, phosphorus pentoxide, aluminum trioxide and a condensation agent.
[0057] Thus, the oxidized carbon black and the hydroxy-terminated polydimethylsiloxane undergo a chemical reaction between carboxyl and hydroxyl groups under the action of the catalyst.
[0058] In practical applications, the above-mentioned surfactant-modified carbon nanotubes can be prepared by first dissolving the surfactant in water to obtain an aqueous surfactant solution, then adding the carbon nanotubes to the aqueous surfactant solution, mixing evenly, ultrasonically treating for a period of time to obtain a suspension, then heating the suspension to reflux for a period of time, filtering out the powder and vacuum drying.
[0059] The surfactant here can include at least one of alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, and high-carbon fatty alcohol polyoxyethylene ether. The surfactant can significantly reduce the surface tension or interfacial tension of the additives in the preparation process of the antistatic masterbatch, thereby promoting the dispersion uniformity of the inorganic filler (carbon black, carbon nanotubes) and improving the performance of the antistatic masterbatch. The surfactant can play a role in surface modification of carbon nanotubes and separate carbon nanotube bundles, thereby improving the dispersion performance of carbon nanotubes.
[0060] In practical applications, the above-mentioned combined dispersant may include oxidized polyethylene wax and a random copolymer, wherein the random copolymer may be a random copolymer formed by copolymerization of an aromatic vinyl monomer and an acrylonitrile monomer. Specifically, the random copolymer may include a random copolymer formed by copolymerization of styrene-acrylonitrile, etc.
[0061] The mass percentage of the oxidized polyethylene wax and the random copolymer can be set in the range of 2 to 4:2 to 1. For example, the mass percentage of the oxidized polyethylene wax and the random copolymer can be 1:1, 2:1, 3:2, 3:1 or 4:1, etc. Thus, the oxidized polyethylene wax and the random copolymer can achieve a better combined dispersion effect together. On the one hand, the melt mass flow rate of the antistatic masterbatch can be improved, and on the other hand, the compatibility of the inorganic filler (carbon black, carbon nanotubes) with the PS resin and the polysiloxane resin can be improved.
[0062] The above-mentioned combined dispersants can play a good combined use effect: on the one hand, the oxidized polyethylene wax can wrap the carbon black, reduce the repulsion between the carbon black and the carbon nanotubes, and improve the mutual penetration between the two, thereby improving the conductivity; on the other hand, the random copolymer can reduce the surface energy of the carbon nanotubes, and at the same time can improve the dispersibility of the carbon black and carbon nanotube combination in the antistatic masterbatch and the matrix resin of the antistatic PS sheet in the process of making products. In short, through the combined synergistic effect of the two dispersants, the overall performance of the antistatic masterbatch is significantly improved.
[0063] In practical applications, the above antioxidants may be high temperature resistant antioxidants, etc. Further, the high temperature resistant antioxidants may be phenol antioxidants, phosphonic acid antioxidants, thiol antioxidants, phenolic resin antioxidants, carbonyl antioxidants, amide antioxidants, etc. Exemplarily, the high temperature resistant antioxidant can be at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester (1010), tris[2,4-di-tert-butylphenyl]phosphite (168), β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (1076), 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (1330), 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (1035), 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid (3144), N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine (1024), 126, etc. It should be noted that 126 is an antioxidant provided by BASF.
[0064] Based on the above, the percentage range of the content of modified carbon black and modified carbon nanotubes in the total amount of antistatic masterbatch prepared in the embodiment of the present application is 50-60%. For example, the percentage of the content of modified carbon black and modified carbon nanotubes in the total amount of antistatic masterbatch can be 50%, 52%, 54%, 56%, 58% or 60%, etc. Therefore, the content of modified carbon black and modified carbon nanotubes in the antistatic masterbatch is relatively high, so that better antistatic properties and surface cleanliness can be achieved.
[0065] Based on the above, the melt mass flow rate of the antistatic masterbatch prepared in the embodiment of the present application is greater than 70g / 10min. Preferably, the melt mass flow rate of the antistatic masterbatch is greater than 100g / 10min. Exemplarily, the melt mass flow rate of the antistatic masterbatch can be 101g / 10min, 105g / 10min, 110g / 10min, 120g / 10min, 130g / 10min or 140g / 10min, etc.
[0066] The embodiment of the present application provides an antistatic masterbatch, by selecting polystyrene resin and polysiloxane resin as the resin of the antistatic masterbatch, at this time, the polysiloxane resin can act as an auxiliary agent of the polystyrene resin to improve the extrusion processing performance of the polystyrene resin; at the same time, the combined dispersant can also improve the dispersion performance of the modified carbon black and the modified carbon nanotubes, and by pre-treating the carbon black into modified carbon black and the carbon nanotubes into modified carbon nanotubes, the dispersion effect of the combined dispersant can also be matched, which greatly improves the dispersion performance of carbon black and carbon nanotubes, and effectively reduces the generation of particles, insolubles, etc. of carbon black and carbon nanotubes. Therefore, when the antistatic masterbatch of the embodiment of the present application is used to make antistatic sheets, the surface dusting and particle problems can be reduced or avoided, the antistatic performance is good, and the performance of the electronic carrier is greatly improved.
[0067] In a second aspect, an embodiment of the present application provides a method for preparing an antistatic masterbatch.
[0068] Before introducing the preparation method of the antistatic masterbatch provided in the embodiments of the present application, the two-stage blending and dispersion method is first introduced.
[0069] The two-stage blending dispersion method can make the conductive filler (such as carbon black, carbon nanotubes, etc. in the embodiments of the present application) dispersed more evenly in the resin, so that the impurities (such as particle points, etc.) in the surface layer material of the product can be controlled within the standard requirements.
[0070] The two-stage blending dispersion method is specifically as follows:
[0071] First, two blending components are provided, and then a part of the component with a larger amount in the two blending components and all of the component with a smaller amount in the two blending components are blended in the first stage. In the first stage of blending, the melt viscosities of the two blending components (two phases) should be made equal as much as possible, and the amounts of the two blending components should also be roughly equal. Under such conditions, a two-phase continuous intermediate product with a "sea-sea structure", i.e., a dual-continuous phase structure, can be prepared.
[0072] In the second stage of the two-stage blending, the remaining part of the material with a higher component content is added to the intermediate product of the "sea-sea structure" to disperse the intermediate product of the "sea-sea structure" to form a "sea-island structure" two-phase system with a dispersed phase having a smaller particle size and a more uniform distribution of the dispersed phase.
[0073] It should be noted that the two blended polymers mentioned above have poor compatibility and form a heterogeneous system after mixing, with the dispersed phase dispersed in the continuous phase, just like small islands dispersed in the ocean, that is, a sea-island structure.
[0074] like Figure 1 As shown, the preparation method of the antistatic masterbatch comprises the following steps:
[0075] S1. The modified carbon black, the modified carbon nanotubes and the combined dispersant are uniformly mixed and dispersed to obtain a conductive mixture.
[0076] S2. The conductive mixture, a part of the polystyrene resin and all of the polysiloxane resin are uniformly mixed, and then heated and kneaded and sliced to obtain a sliced material.
[0077] S3. Blending the sliced material and the remaining part of the polystyrene resin, melt-extrude and granulate to obtain an antistatic masterbatch.
[0078] Furthermore, if Figure 2 As shown, the above step S3. blending the sliced material and the remaining part of the polystyrene resin, and melt-extruding and granulating to obtain the antistatic masterbatch may include:
[0079] S31. Blending the sliced material, the remaining part of the polystyrene resin and the antioxidant, melt-extruding and granulating, to obtain an antistatic masterbatch.
[0080] like Figure 3 As shown, the preparation method of the modified carbon black comprises the following steps:
[0081] S101. Evenly mix the carbon black powder and concentrated acid at 60-130° C., wash until neutral, and dry to obtain oxidized carbon black.
[0082] S102. Evenly mix the oxidized carbon black, the terminal hydroxyl polydimethylsiloxane and the catalyst at 50 to 140° C. to obtain modified carbon black.
[0083] like Figure 4 As shown, the preparation method of the modified carbon nanotubes comprises the following steps:
[0084] S201. Dissolve the surfactant in water to obtain a surfactant aqueous solution.
[0085] S202. Add carbon nanotubes to the surfactant aqueous solution, mix well, and perform ultrasonic treatment for a period of time to obtain a suspension.
[0086] S203. The suspension is heated to reflux for a period of time, and then the powder is filtered out and vacuum dried to obtain modified carbon nanotubes.
[0087] It should be noted that there is no specific limitation on the preparation order of the modified carbon black and the modified carbon nanotubes. The modified carbon black may be prepared first and then the modified carbon nanotubes; or the modified carbon nanotubes may be prepared first and then the modified carbon black; or the modified carbon black and the modified carbon nanotubes may be prepared at the same time.
[0088] The specific preparation method of the antistatic masterbatch of the embodiment of the present application is given below:
[0089] 1. Preparation of modified carbon black:
[0090] (1) Add carbon black and concentrated acid into a three-necked flask, stir and react at 60-130°C for 5-24 hours, wash with deionized water until neutral, and then dry at 50-140°C to obtain oxidized carbon black.
[0091] (2) Stir oxidized carbon black, terminal hydroxyl polydimethylsiloxane and catalyst at 50-140°C for 4-10 hours to obtain modified carbon black.
[0092] 2. Preparation of modified carbon nanotubes:
[0093] (1) Dissolve the surfactant in water to obtain a surfactant aqueous solution.
[0094] The mass percentage of the surfactant content in the surfactant aqueous solution is in the range of 2 to 8 wt%. For example, the mass percentage of the surfactant content in the surfactant aqueous solution may be 2 wt%, 3 wt%, 4 wt% or 5 wt%.
[0095] (2) Add carbon nanotubes to the surfactant aqueous solution, stir and mix, and place in ultrasonic vibration for 1 to 3 hours to obtain a suspension.
[0096] The mass percentage of the carbon nanotube content in the suspension is in the range of 1-4wt%. For example, the mass percentage of the carbon nanotube content in the suspension may be 1wt%, 2wt%, 3wt% or 4wt%.
[0097] (3) Heat the suspension to reflux for 2 to 5 hours, then remove the powder by vacuum filtration and dry it in a vacuum drying oven to obtain modified carbon nanotubes.
[0098] 3. Add modified carbon nanotubes and a combined dispersant to the modified carbon black, mix and stir, and perform ball milling to disperse the mixture to obtain a conductive mixture.
[0099] The maximum particle size Dmax of the conductive mixture is ≤50 nm. For example, the Dmax of the conductive mixture may be 10 nm, 20 nm, 30 nm, 40 nm or 50 nm, etc. The conductive mixture has a small particle size, which can achieve better dispersion.
[0100] (2) The conductive mixture, a part of the polystyrene resin and all of the polydimethylsiloxane are stirred and mixed, heated and kneaded, and then sliced.
[0101] The above-mentioned internal mixing is equivalent to pre-dispersion.
[0102] The percentage of the total mass of the above-mentioned part of the polystyrene resin in the total polystyrene resin can range from 30 to 50%. For example, the percentage of the total mass of the part of the polystyrene resin in the total polystyrene resin can be 30%, 35%, 40%, 45%, 48% or 50%, etc.
[0103] 4. After preheating the twin screws, add the sliced material, antioxidant and the remaining polystyrene resin, blend and melt-extrude to form granules, and obtain the antistatic masterbatch.
[0104] In application, the granules can be melt-extruded by a twin-screw extruder.
[0105] The twin-screw extruder sequentially comprises a melting section, a first extrusion section, a first shearing section, a first pressurizing section, a first melting and exhausting section, a second extrusion section, a second shearing section, a second pressurizing section, a second melting and exhausting section and a die.
[0106] The set process conditions of the twin-screw extruder are as follows: the temperature range of the melting section is 200-210°C, the temperature range of the first extrusion section is 215-225°C, the temperature range of the first shearing section is 220-230°C, the temperature range of the first pressurizing section is 225-235°C, the temperature range of the first melt-venting section is 225-235°C, the temperature range of the second extrusion section is 230-240°C, the temperature range of the second shearing section is 230-240°C, the temperature range of the second pressurizing section is 225-235°C, the temperature range of the second melt-venting section is 200-230°C, and the temperature range of the die is 215-235°C.
[0107] The main engine speed of the twin-screw extruder is 400-1000 rpm / min. Exemplarily, the main engine speed of the twin-screw extruder can be 400 rpm / min, 500 rpm / min, 700 rpm / min, 800 rpm / min, 900 rpm / min or 1000 rpm / min.
[0108] The vacuum degree of the twin-screw extruder is ≤-0.05 MPa. For example, the vacuum degree of the twin-screw extruder may be -0.1 MPa, -0.09 MPa, -0.08 MPa, -0.07 MPa, -0.06 MPa or -0.05 MPa, etc.
[0109] The embodiment of the present application provides a method for preparing an antistatic masterbatch, which makes the carbon black and carbon nanotubes dispersed very evenly, reduces the generation of particles and insoluble matter, and is simple and easy to implement through the selection of resin combinations, pretreatment of carbon black and carbon nanotubes, selection of dispersants, and combined with adjustment of the order of adding materials in the preparation process of the antistatic masterbatch and the use of a blending process.
[0110] The following uses a number of specific examples to illustrate the preparation method and application of the antistatic masterbatch in the examples of the present application and the masterbatch in the comparative example.
[0111] 1. Antistatic masterbatch and preparation method thereof of the present application:
[0112] Example 1
[0113] 1. Recipe:
[0114] PS resin, 30 parts; polysiloxane, 15 parts; concentrated nitric acid-modified carbon black, 40 parts; alkylphenol polyoxyethylene ether-modified carbon nanotubes, 5 parts; oxidized polyethylene wax + styrene-acrylonitrile random copolymer, 12 parts, including oxidized polyethylene wax 8 parts and styrene-acrylonitrile random copolymer 4 parts; antioxidant, 3 parts.
[0115] 2. Preparation:
[0116] (1) Add carbon black and concentrated nitric acid into a three-necked flask, stir and react at 100°C for 8 hours, wash with deionized water until neutral, and dry at 50°C to obtain oxidized carbon black; then stir the oxidized carbon black with terminal hydroxyl polydimethylsiloxane in the presence of a catalyst at 50°C for 4 hours to obtain concentrated nitric acid-modified carbon black.
[0117] (2) Dissolve alkylphenol polyoxyethylene ether in water (the mass concentration of alkylphenol polyoxyethylene ether in the aqueous solution is 5wt%), add carbon nanotubes to the aqueous solution of alkylphenol polyoxyethylene ether, stir and mix, and place in ultrasonic vibration for 1 hour to form a suspension (the mass percentage of carbon nanotube content in the suspension is 1wt%), then heat the suspension to reflux for 2 hours, then filter out the powder by vacuum and dry it in a vacuum drying oven to obtain carbon nanotubes modified with alkylphenol polyoxyethylene ether.
[0118] (3) Add carbon nanotubes modified with alkylphenol polyoxyethylene ether, oxidized polyethylene wax and a dispersant consisting of a styrene-acrylonitrile random copolymer (the mass ratio of oxidized polyethylene wax to styrene-acrylonitrile random copolymer is 2:1) to the carbon black modified with concentrated nitric acid, stir and disperse by ball milling to obtain a conductive mixture with a Dmax of 10 nm.
[0119] (4) The conductive mixture, 30% of the PS resin and all the polydimethylsiloxane are stirred and mixed, heated and kneaded, and then sliced.
[0120] (5) After preheating the twin screw, add the sliced material, antioxidant and the remaining PS resin, blend and melt extrude to granulate, and then obtain the antistatic masterbatch.
[0121] Example 2
[0122] 1. Recipe:
[0123] PS resin, 40 parts; polysiloxane, 30 parts; concentrated nitric acid-modified carbon black, 60 parts; fatty acid polyoxyethylene ester-modified carbon nanotubes, 15 parts; oxidized polyethylene wax + styrene-acrylonitrile random copolymer, 25 parts, including oxidized polyethylene wax 12.5 parts and styrene-acrylonitrile random copolymer 12.5 parts; antioxidant, 2 parts.
[0124] 2. Preparation:
[0125] (1) Add carbon black and concentrated nitric acid into a three-necked flask, stir and react at 90°C for 10 hours, wash with deionized water until neutral, and dry at 80°C to obtain oxidized carbon black; then stir the oxidized carbon black with terminal hydroxyl polydimethylsiloxane in the presence of a catalyst at 80°C for 6 hours to obtain concentrated nitric acid-modified carbon black.
[0126] (2) Dissolve fatty acid polyoxyethylene ester in water (the mass concentration of fatty acid polyoxyethylene ester in the aqueous solution is 6wt%), add carbon nanotubes to the aqueous solution of fatty acid polyoxyethylene ester, stir and mix, and place in ultrasonic vibration for 2h to form a suspension (the mass percentage of carbon nanotube content in the suspension is 2wt%), then heat the suspension under reflux for 3h, and then filter out the powder by vacuum drying and dry in a vacuum drying oven to obtain alkylphenol polyoxyethylene ether modified carbon nanotubes.
[0127] (3) Add carbon nanotubes modified with polyoxyethylene fatty acid esters, oxidized polyethylene wax and a dispersant consisting of a styrene-acrylonitrile random copolymer (the mass ratio of the oxidized polyethylene wax to the styrene-acrylonitrile random copolymer is 1:1) to the carbon black modified with concentrated nitric acid, mix and stir, and disperse by ball milling to obtain a conductive mixture with a Dmax of 20 nm.
[0128] (4) The conductive mixture, 50% of the PS resin and all the polydimethylsiloxane are stirred and mixed, heated and kneaded, and then sliced.
[0129] (5) After preheating the twin screw, add the sliced material, antioxidant and the remaining PS resin, blend and melt extrude to granulate, and then obtain the antistatic masterbatch.
[0130] Example 3
[0131] 1. Recipe:
[0132] PS resin, 35 parts; polysiloxane, 20 parts; carbon black modified with concentrated nitric acid, 50 parts; carbon nanotubes modified with high-carbon fatty alcohol polyoxyethylene ether, 10 parts; oxidized polyethylene wax + styrene-acrylonitrile random copolymer, 16 parts, including oxidized polyethylene wax 12 parts and styrene-acrylonitrile random copolymer 4 parts; antioxidant, 1 part.
[0133] 2. Preparation:
[0134] (1) Add carbon black and concentrated nitric acid into a three-necked flask, stir and react at 70°C for 12 hours, wash with deionized water until neutral, and dry at 100°C to obtain oxidized carbon black; then stir the oxidized carbon black with terminal hydroxyl polydimethylsiloxane in the presence of a catalyst at 100°C for 7 hours to obtain concentrated nitric acid-modified carbon black.
[0135] (2). Dissolve high-carbon fatty alcohol polyoxyethylene ether in water (the mass concentration of high-carbon fatty alcohol polyoxyethylene ether in the aqueous solution is 8wt%), add carbon nanotubes to the aqueous solution of high-carbon fatty alcohol polyoxyethylene ether, stir and mix, and place it in ultrasonic vibration for 3 hours to form a suspension (the mass percentage of carbon nanotube content in the suspension is 3wt%), then heat the suspension under reflux for 5 hours, and then vacuum filter to remove the powder and dry it in a vacuum drying oven to obtain alkylphenol polyoxyethylene ether modified carbon nanotubes.
[0136] (3) Add carbon nanotubes modified with high-carbon fatty alcohol polyoxyethylene, oxidized polyethylene wax and a dispersant consisting of a styrene-acrylonitrile random copolymer (the mass ratio of oxidized polyethylene wax to styrene-acrylonitrile random copolymer is 3:1) to the carbon black modified with concentrated nitric acid, mix and stir, and disperse by ball milling to obtain a conductive mixture with a Dmax of 30 nm.
[0137] (4) The conductive mixture, 40% of the PS resin and all the polydimethylsiloxane are stirred and mixed, heated and kneaded, and then sliced.
[0138] (5) After preheating the twin screw, add the sliced material, antioxidant and the remaining PS resin, blend and melt extrude to granulate, and then obtain the antistatic masterbatch.
[0139] Example 4
[0140] 1. Recipe:
[0141] PS resin, 32 parts; polysiloxane, 18 parts; carbon black modified with concentrated nitric acid, 48 parts; carbon nanotubes modified with alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester and high-carbon fatty alcohol polyoxyethylene ether, 8 parts; oxidized polyethylene wax + styrene-acrylonitrile random copolymer, 15 parts, including oxidized polyethylene wax 10 parts and styrene-acrylonitrile random copolymer 5 parts; antioxidant, 2 parts.
[0142] 2. Preparation:
[0143] (1) Add carbon black and concentrated nitric acid into a three-necked flask, stir and react at 80°C for 15 hours, wash with deionized water until neutral, and dry at 110°C to obtain oxidized carbon black; then stir the oxidized carbon black with terminal hydroxyl polydimethylsiloxane in the presence of a catalyst at 110°C for 8 hours to obtain concentrated nitric acid-modified carbon black.
[0144] (2) Dissolve alkylphenol polyoxyethylene ether in water (the mass concentration of alkylphenol polyoxyethylene ether in the aqueous solution is 3wt%), add carbon nanotubes to the aqueous solution of alkylphenol polyoxyethylene ether, stir and mix, and place it in ultrasonic vibration for 1 hour to form a suspension (the mass percentage of carbon nanotube content in the suspension is 4wt%), then heat the suspension under reflux for 2 hours, then filter out the powder by vacuum and dry it in a vacuum drying oven to obtain carbon nanotubes modified with alkylphenol polyoxyethylene ether.
[0145] (3) Add carbon nanotubes modified with alkylphenol polyoxyethylene ether, oxidized polyethylene wax and a dispersant consisting of a styrene-acrylonitrile random copolymer (the mass ratio of the oxidized polyethylene wax to the styrene-acrylonitrile random copolymer is 2:1) to the carbon black modified with concentrated nitric acid, stir and mix, and perform ball milling to obtain a conductive mixture. The Dmax of the conductive mixture is 40 nm.
[0146] (4) The conductive mixture, 30%, 35%, 40%, 45%, 48%, 50% of the total amount of PS resin and all the polydimethylsiloxane are stirred and mixed, heated and kneaded, and then sliced.
[0147] (5) After preheating the twin screw, add the sliced material, antioxidant and the remaining PS resin, blend and melt extrude to granulate, and then obtain the antistatic masterbatch.
[0148] Example 5
[0149] 1. Recipe:
[0150] PS resin, 36 parts; polysiloxane, 23 parts; carbon black modified with concentrated nitric acid, 53 parts; carbon nanotubes modified with alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester and high-carbon fatty alcohol polyoxyethylene ether, 13 parts; oxidized polyethylene wax + styrene-acrylonitrile random copolymer, 20 parts, including oxidized polyethylene wax 16 parts and styrene-acrylonitrile random copolymer 4 parts; antioxidant, 3 parts.
[0151] 2. Preparation:
[0152] (1) Add carbon black and concentrated nitric acid into a three-necked flask, stir and react at 60°C for 18 hours, wash with deionized water until neutral, and dry at 120°C to obtain oxidized carbon black; then stir the oxidized carbon black with terminal hydroxyl polydimethylsiloxane in the presence of a catalyst at 120°C for 9 hours to obtain concentrated nitric acid-modified carbon black.
[0153] (2) Dissolve fatty acid polyoxyethylene ester in water (the mass concentration of fatty acid polyoxyethylene ester in the aqueous solution is 3wt%), add carbon nanotubes to the aqueous solution of fatty acid polyoxyethylene ester, stir and mix, and place in ultrasonic vibration for 2h to form a suspension (the mass percentage of carbon nanotube content in the suspension is 1wt%), then heat the suspension to reflux for 4h, then vacuum filter to remove the powder and dry it in a vacuum drying oven to obtain fatty acid polyoxyethylene ester modified carbon nanotubes.
[0154] (3) Add carbon nanotubes modified with polyoxyethylene fatty acid esters, oxidized polyethylene wax and a dispersant consisting of a styrene-acrylonitrile random copolymer (the mass ratio of the oxidized polyethylene wax to the styrene-acrylonitrile random copolymer is 4:1) to the carbon black modified with concentrated nitric acid, stir and disperse by ball milling to obtain a conductive mixture with a Dmax of 45 nm.
[0155] (4) The conductive mixture, 48% of the PS resin and all the polydimethylsiloxane are stirred and mixed, heated and kneaded, and then sliced.
[0156] (5) After preheating the twin screw, add the sliced material, antioxidant and the remaining PS resin, blend and melt extrude to granulate, and then obtain the antistatic masterbatch.
[0157] Example 6
[0158] 1. Recipe:
[0159] PS resin, 38 parts; polysiloxane, 26 parts; carbon black modified with concentrated nitric acid, 56 parts; carbon nanotubes modified with alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester and high-carbon fatty alcohol polyoxyethylene ether, 16 parts; oxidized polyethylene wax + styrene-acrylonitrile random copolymer, 24 parts, including oxidized polyethylene wax 16 parts and styrene-acrylonitrile random copolymer 8 parts; antioxidant, 3 parts.
[0160] 2. Preparation:
[0161] (1) Add carbon black and concentrated nitric acid into a three-necked flask, stir and react at 130°C for 24 hours, wash with deionized water until neutral, and dry at 140°C to obtain oxidized carbon black; then stir the oxidized carbon black with terminal hydroxyl polydimethylsiloxane in the presence of a catalyst at 140°C for 10 hours to obtain concentrated nitric acid-modified carbon black.
[0162] (2). Dissolve high-carbon fatty alcohol polyoxyethylene ether in water (the mass concentration of high-carbon fatty alcohol polyoxyethylene ether in the aqueous solution is 4wt%), add carbon nanotubes to the aqueous solution of high-carbon fatty alcohol polyoxyethylene ether, stir and mix, and place it in ultrasonic vibration for 3h to form a suspension (the mass percentage of carbon nanotube content in the suspension is 2wt%), then heat the suspension to reflux for 4h, then vacuum filter to remove the powder and dry it in a vacuum drying oven to obtain high-carbon fatty alcohol polyoxyethylene ether modified carbon nanotubes.
[0163] (3) Add carbon nanotubes modified with high-carbon fatty alcohol polyoxyethylene ether, oxidized polyethylene wax and a dispersant consisting of styrene-acrylonitrile random copolymer (the mass ratio of oxidized polyethylene wax to styrene-acrylonitrile random copolymer is 2:1) to the carbon black modified with concentrated nitric acid, mix and stir, and perform ball milling to obtain a conductive mixture. The Dmax of the conductive mixture is 50 nm.
[0164] (4) The conductive mixture, 50% of the PS resin and all the polydimethylsiloxane are stirred and mixed, heated and kneaded, and then sliced.
[0165] (5) After preheating the twin screw, add the sliced material, antioxidant and the remaining PS resin, blend and melt extrude to granulate, and then obtain the antistatic masterbatch.
[0166] 2. Comparative Example of Masterbatch and Preparation Method thereof:
[0167] Comparative Example 1
[0168] Compared with Example 1, the only difference is that the carbon black and the carbon nanotubes are not pretreated.
[0169] The other preparation processes are the same as those in Example 1 and will not be described again here.
[0170] Comparative Example 2
[0171] Compared with Example 1, the only difference is that the dispersant is only oxidized polyethylene wax.
[0172] The other preparation processes are the same as those in Example 1 and will not be described again here.
[0173] Comparative Example 3
[0174] Compared with Example 1, the only difference is that the components contained in the formula do not contain polysiloxane resin.
[0175] formula:
[0176] PS resin, 30 parts; polysiloxane, 15 parts; concentrated nitric acid-modified carbon black, 40 parts; alkylphenol polyoxyethylene ether-modified carbon nanotubes, 5 parts; oxidized polyethylene wax + styrene-acrylonitrile random copolymer, 12 parts, including oxidized polyethylene wax 8 parts and styrene-acrylonitrile random copolymer 4 parts; antioxidant, 3 parts.
[0177] The other preparation processes are the same as those in Example 1 and will not be described again here.
[0178] Comparative Example 4
[0179] Compared with Example 1, the only difference is that the carbon black is not pretreated.
[0180] The other preparation processes are the same as those in Example 1 and will not be described again here.
[0181] Comparative Example 5
[0182] Compared with Example 1, the only difference is that the carbon nanotubes are not pretreated.
[0183] The other preparation processes are the same as those in Example 1 and will not be described again here.
[0184] Comparative Example 6
[0185] Compared with Example 1, the only difference is that the dispersant is only styrene-acrylonitrile random copolymer.
[0186] The other preparation processes are the same as those in Example 1 and will not be described again here.
[0187] Performance Testing
[0188] 4500g of high impact polystyrene (HIPS) resin and 150g of toughening agent were mixed uniformly with 1000g of antistatic masterbatch prepared in Examples 1 to 6 and masterbatch prepared in Comparative Examples 1 to 6 at room temperature, and then a granular durable antistatic HIPS composite material was prepared at 240°C using a twin-screw granulator.
[0189] The above antistatic HIPS composite material was injection molded into test specimens according to standard size, and the tensile strength, flexural strength, impact strength, surface average resistivity, surface resistivity and surface flatness of each sample were tested respectively. The test results are shown in Table 1 below.
[0190] The tensile strength test method is as follows: in accordance with ISO 527:2010(E) standard, the test is carried out under the test conditions of 5Kg and 50°C / h.
[0191] The testing method for bending strength is as follows: testing is carried out at a testing speed of 2 mm / min in accordance with ISO 178:2010(E) standard.
[0192] Impact strength: tested in accordance with ISO 179-1:2010(E) at 23°C with an impact energy of 4J.
[0193] The test method for surface resistivity is: the DC comparison method is used during the test, 10 positions on the front and back sides of the test specimen are tested, and the test equipment and measurement error comply with the provisions of GB / T 3048.5.
[0194] The surface average resistivity is the average value of the above-mentioned surface resistivities.
[0195] The surface flatness was obtained by observing the surface of each test specimen through a microscope.
[0196] The above performance test results are shown in Table 1 below.
[0197] Table 1
[0198]
[0199]
[0200] As can be seen from Table 1, compared with Comparative Example 1, Example 1 of the present application only uses unmodified carbon black to replace the modified carbon black in Example 1, and unmodified carbon nanotubes to replace the modified carbon nanotubes in Example 1. Since the carbon black and carbon nanotubes in Comparative Example 1 are not modified, they cannot be evenly dispersed in the antistatic masterbatch, and the antistatic performance of the antistatic masterbatch is poor. This leads to a decrease in the uniformity and average resistivity of the surface resistivity of the product. At the same time, the tensile strength, bending strength and impact strength of the product are low, so the mechanical properties of the product are poor. In addition, the surface flatness of the product is also poor.
[0201] Compared with Example 2, Example 1 of the present application uses only oxidized polyethylene wax instead of the combination of oxidized polyethylene wax and styrene-acrylonitrile random copolymer in Example 1 as a dispersant in Example 2. Since Comparative Example 2 uses only a single dispersant, carbon black and carbon nanotubes cannot be evenly dispersed in the antistatic masterbatch, and the antistatic performance of the antistatic masterbatch is poor. This leads to a decrease in the uniformity and average resistivity of the surface resistivity of the product. At the same time, the tensile strength, bending strength and impact strength of the product are low, so the mechanical properties of the product are poor. In addition, the surface flatness of the product is slightly poor.
[0202] Compared with Example 3, Example 1 of the present application only uses PS resin to replace the combination of PS resin and polysiloxane resin in Example 1 as the resin of the antistatic masterbatch in Example 3. Since polysiloxane resin is not used in Comparative Example 3, carbon black cannot be evenly dispersed in the antistatic masterbatch, and the processing performance of PS resin extrusion cannot be improved, and the antistatic performance of the antistatic masterbatch is poor. This leads to a decrease in the uniformity and average resistivity of the surface resistivity of the product. At the same time, the tensile strength, bending strength and impact strength of the product are low, so the mechanical properties of the product are poor. In addition, the surface flatness of the product is also poor.
[0203] Compared with Example 4, Example 1 of the present application uses only unmodified carbon black to replace the modified carbon black in Example 1. Since the carbon black in Example 4 is unmodified, the carbon black and carbon nanotubes cannot be evenly dispersed in the antistatic masterbatch, and the antistatic performance of the antistatic masterbatch is poor. This leads to a decrease in the uniformity and average resistivity of the surface resistivity of the product. At the same time, the tensile strength, bending strength and impact strength of the product are low, so the mechanical properties of the product are poor. In addition, the surface flatness of the product is also poor.
[0204] Compared with Example 5, Example 1 of the present application uses only unmodified carbon nanotubes to replace the modified carbon nanotubes in Example 1. Since the carbon nanotubes in Example 5 are not modified, carbon black and carbon nanotubes cannot be evenly dispersed in the antistatic masterbatch, and the antistatic performance of the antistatic masterbatch is poor. This leads to a decrease in the uniformity and average resistivity of the surface resistivity of the product. At the same time, the tensile strength, bending strength and impact strength of the product are low, so the mechanical properties of the product are poor. In addition, the surface flatness of the product is also poor.
[0205] Compared with Example 6, Example 1 of the present application uses only styrene-acrylonitrile random copolymer to replace the combination of oxidized polyethylene wax and styrene-acrylonitrile random copolymer in Example 1 as a dispersant. Since Comparative Example 6 uses only a single dispersant, carbon black and carbon nanotubes cannot be evenly dispersed in the antistatic masterbatch, and the antistatic performance of the antistatic masterbatch is poor. This leads to a decrease in the uniformity and average resistivity of the surface resistivity of the product. At the same time, the tensile strength, bending strength and impact strength of the product are low, so the mechanical properties of the product are poor. In addition, the surface flatness of the product is slightly poor.
[0206] Compared with Example 1, Examples 2 to 6 of the present application are slightly different in the formula of the antistatic masterbatch and some parameters in the process. Therefore, compared with Comparative Examples 1 to 6, Examples 2 to 6 can improve the extrusion processing performance of polystyrene resin, and at the same time, the dispersion stability of carbon black and carbon nanotubes is better, the generation of carbon black and carbon nanotube particles, insoluble matter, etc. is reduced, and the antistatic performance is good. In addition, the tensile strength, bending strength and impact strength of the product are good, and the number of foreign matter on the surface of the product is small, the cleanliness is also good, and the surface flatness is high.
[0207] Only the contents related to the invention are introduced here. The rest can be obtained by referring to the relevant technology and will not be described in detail here.
[0208] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. An antistatic masterbatch, characterized in that: The parts by weight include: Polystyrene resin, 30-40 parts; Polysiloxane resin, 15-30 parts; Modified carbon black, 40-60 parts; wherein the modified carbon black is acid-modified carbon black; 5 to 20 parts of modified carbon nanotubes; wherein the modified carbon nanotubes are carbon nanotubes modified by surfactants; Combined dispersant, 15 to 30 parts.
2. The antistatic masterbatch according to claim 1, characterized in that: The percentage range of the modified carbon black and the modified carbon nanotube in the total amount of the antistatic masterbatch is 50-60%; and / or, The melt mass flow rate of the antistatic masterbatch is greater than 70 g / 10 min.
3. The antistatic masterbatch according to claim 1 or 2, characterized in that: The surfactant includes at least one of alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester and high-carbon fatty alcohol polyoxyethylene ether.
4. The antistatic masterbatch according to claim 1 or 2, characterized in that: The polysiloxane resin includes polydimethylsiloxane.
5. The antistatic masterbatch according to claim 1 or 2, characterized in that: The combined dispersant comprises oxidized polyethylene wax and a random copolymer, wherein the random copolymer is formed by copolymerization of an aromatic vinyl monomer and an acrylonitrile monomer.
6. The antistatic masterbatch according to claim 5, characterized in that: The mass percentage range of the oxidized polyethylene wax and the random copolymer is 2-4:2-1.
7. An antistatic sheet, characterized in that: The invention comprises the antistatic masterbatch as described in any one of claims 1 to 6.
8. A method for preparing an antistatic masterbatch according to any one of claims 1 to 6, characterized in that: The steps include: The modified carbon black, the modified carbon nanotubes and the combined dispersant are uniformly mixed and dispersed to obtain a conductive mixture; The conductive mixture, a part of the polystyrene resin and all the polysiloxane resin are uniformly mixed, heated and kneaded, and then sliced to obtain a sliced material; The sliced material and the remaining part of the polystyrene resin are blended, melted, extruded and granulated to obtain the antistatic masterbatch; Wherein, the maximum particle size of the conductive mixture is less than or equal to 50 nm; and / or, the amount of the part of polystyrene resin is in the range of 30-50% of the total mass of the whole polystyrene resin.
9. The method for preparing the antistatic masterbatch according to claim 8, characterized in that: The preparation method of the modified carbon black comprises the following steps: The carbon black and concentrated acid are mixed evenly at 60-130°C, washed to neutrality, and dried to obtain oxidized carbon black; The oxidized carbon black, the terminal hydroxyl polydimethylsiloxane and the catalyst are uniformly mixed at 50 to 140° C. to obtain the modified carbon black.
10. The method for preparing the antistatic masterbatch according to claim 8, characterized in that: The preparation method of the modified carbon nanotubes comprises the following steps: dissolving a surfactant in water to obtain a surfactant aqueous solution; Adding carbon nanotubes to the surfactant aqueous solution, mixing evenly, and ultrasonically treating for a period of time to obtain a suspension; The suspension is heated and refluxed for a period of time, and then the powder is filtered out and vacuum dried to obtain the modified carbon nanotubes.
Citation Information
Patent Citations
Antistatic polycarbonate, and preparation method thereof
CN109181268A
Antistatic composite material as well as preparation method and application thereof
CN117362971A
Antistatic composite material as well as preparation method and application thereof
CN117645762A
An electrically conductive resin composition and a method for preparing the same
KR102084640B1
High-impact-resistance polystyrene composite material, preparation method therefor, and product thereof
WO2024140413A1